Aligning strategy, management, and pedagogy: A grounded theory of sustainability learning in short-term ASEAN mobility - Simek, Lea; Adhisti, Mita (Journal of International Students, 2026)
Aligned with the ASEAN Economic Community’s (AEC) vision for regional integration and sustainable development, universities are expected to advance internationalization through mobility, research, and community engagement. However, the sustainability learning outcomes of short-term mobility programs remain underexplored. This case study examines a six-week hybrid mobility initiative between an Indonesian private university and a Singaporean partner. Using a grounded theory approach and discussions with students and staff, the study explores how program design and institutional support shape outcomes. The findings indicate that students gained modest benefits, including social connections and introductory sustainability, but learning was constrained by compressed timelines and unclear roles. Staff highlighted the need for clearer prioritization and stronger alignment with institutional goals. The study proposes a model in which outcomes depend on the alignment of strategy, program management, and pedagogy, offering a framework to strengthen short-term hybrid mobility programs in ASEAN higher education and beyond.